A Comprehensive Study on Availability of Anti-cancer drugs in Dhaka City, Bangladesh (Bangladesh Pharmaceutical Journal, 2020)
With the increasing rate of people being affected by cancer in Bangladesh, the disease has become a national concern. Anti-cancer drugs play a significant and crucial role in cancer treatment regimen. Inadequate access to essential anti-cancer medicines may impose serious public health problems in Bangladesh. The present study gives an insight on the availability of eleven WHO enlisted essential anticancer drugs that are commonly prescribed for the top five prevalent cancer types (Breast, Oesophagus, Lung, Cervix, Lips and Oral cavity) in Bangladesh. Expert advice on which essential anti-cancer medicines are commonly prescribed were gathered from oncologists of three medical college hospitals (Dhaka Medical College Hospital (DMCH), Bangabandhu Sheikh Mujib Medical University (BSMMU) and National Institute of Cancer Research and Hospital (NICRH). The study was conducted among a total of 151 pharmaceutical drug stores including 119 retail, 27 model and 5 hospital pharmacies. The sample size of 151 pharmacies was calculated for 4547 pharmacies in Dhaka district with 95% confidence interval and 8% margin of error. It was found that 74% of the pharmacy stores surveyed kept no anti-cancer drugs at all. There is a significant negative relationship between price and availability of oncology medicine for which Pearson’s correlation co-efficient ‘r’ is found to be -0.739 (p=0.01). This means that high priced medicines are less available. Pharmacy stores keep anti-cancer drugs from both local (81.9%) and foreign (18.1%) pharmaceutical companies. In order to evaluate sales performance of pharmacies in context of oncology drugs, monthly number of cancer patients buying medicines from these pharmacies has been studied as well. It has been found that supply of anti-cancer drugs by pharmaceutical companies among medicine stores is not homogenous. Availability and sales rate of oncology products in some pharmacies situated within the same area is way more than others and the number of customer (cancer patient) varies by wide margins. A comparative analysis on availability rate of model versus retail pharmacies in different areas of Dhaka city has been carried out. Retail pharmacies near cancer-care hospitals tend to keep more anti-cancer medicines compared to those situated away from cancer-care hospitals.Bangladesh Pharmaceutical Journal 23(2): 155-166, 2020